Employee-Employer Interaction from the Specificity of Work Training Perspective - NEGULESCU, Mihail-Cristian; BARBU, Cristina -Mihaela (Journal of Advanced Research in Management; Vol 12 No 1 (2021): JARM Volume XII Issue 1 (23) Summer 2021, 2021)
The rapid process of restructuring the value system and the fundamental reorganization of life as a whole, including professional life, highlights the major implications of the human group as a form of action and balance of the contradictory relationships manifested on a psycho-moral background at the organizational level. Therefore, at the organizational level, the man of the future, the new type man, the complex man, the organizational man, who will be characterized by the measure of his complexity, tending to identify with organizational objectives, will play a fundamental role. The characteristic of accepting the organizational objectives, pursuing their fulfillment, the man of the future, the employee of tomorrow, will highlight the inter-relationship between him and the organization in order to obtain the planned results. In such context, supported by the thesis regarding the usefulness of the existence of appreciable differences between individuals and motivational factors, managers can use flexible strategies to achieve organizational goals using maximum human and professional capabilities of employees, formed in formal working groups or in work teams.